Outsourcing library technical services operations practices in academic and special libraries in Metro Manila - Ramos, Marian S.; Yang, Jackson V.; Santos, Herminia H. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2004)
Outsourcing, which requires strategic decision and proactive professional decision-making, is a mainstream strategy of a business sector but its concept is not new to librarians. Outsourcing is the term given to the practice of contracting and internal activities or processes that would otherwise be performed by in-house employees to an external company or a group of individuals.
This study has six parts: Part One, includes the profile of the respondents; Part Two, investigates the degree of agreement in ranking the outsourcing advantages and disadvantages; Part Three, identifies the most important advantages and disadvantages of outsourcing; Part Four, examines the relationships of the variables as hypothesized in the study; Part Five, describes the outsourcing practices of De La Salle University (DLSU) Library, Philippine Council for Health Research and Development (PCHRD) Library, and the Isis International-Manila Women's Resource and Information Centre; and Part Six, analyzes the similarities and differences in the practices of the currently and formerly outsourcing libraries.
The design of this research involves the case study approach as well as the quantitative approach using confidence interval estimation for proportion, Kendall's coefficient of concordance and chi-square statistics. The populations of this study were 90 special libraries and 61 academic libraries in Metro Manila listed in PAARL, PLAI and ASLP directories, whether there are currently outsourcing, have previously outsourced, or have never outsourced technical services operations. To get the sample size of each population, the confidence level was set at 95 percent and the margin of error to (plus minus) 10. For the case study approach, the researcher chose two special libraries and one academic library among libraries which are currently and formerly outsourcing technical functions as subjects. De La Salle University Library (Manila), Philippine Council for Health Research and Development (PCHRD) Library, and the Isis International-Manila Women's Resource and Information Center were chosen as the subjects for the case study. A structured survey questionnaire was used as an instrument. The researcher devised two survey questionnaires: one for the descriptive approach and the other one as a guiding questionnaire for the case study approach.
The study found that outsourcing of technical services operations is not prevalent among special and academic libraries in Metro Manila. The following are the reasons of libraries that have never outsourced, for not engaging in outsourcing initiatives: (1) loss of in-house expertise; (2) damage of cooperative efforts; (3) lack of support from senior management; (4) providers do not perform as promised; (5) outsourcing program is not well aligned with the organization's strategies; and, (6) library staff can still manage to perform the functions in-house. When respondents were asked as to why they would consider to outsource technical functions in the future, they responded with the following reasons: (1) to lessen workload; (2) to focus on more important areas of library services; (3) cost-effectiveness for digitization project in particular; (4) to update information technology and library modernization; (5) to fulfill the organization's mission and objectives effectively and efficiently; (6) to eliminate backlogs; and, (7) lack of manpower to perform the job.
In general, there is a low degree of agreement among respondents by type of libraries in the judgments of outsourcing advantages and disadvantages and concluded that there is a significant positive association. Among academic libraries, the most important outsourcing advantages is "productivity can be greatly enhanced when outsourcing is used for reducing backlogs, processing material in special/format, developing opening collection or managing ongoing technical services operations" while the least important advantage is "opportunities typically arise in which staff can be reallocated to other areas to perform new tasks," respectively. The most important disadvantage is the start-up costs of outsourcing projects while the least important outsourcing disadvantage is the start-up costs of outsourcing projects while the least important outsourcing disadvantage is the possible increase in turnaround time. among special libraries, to "enable staff to focus on core competencies and improve customer services that cannot be outsources" " is the most important outsourcing advantage while to "reduce on-the-job injuries resulting from Repetitive Motion Syndrome" is the least important advantage. In terms of outsourcing disadvantage, "long period of planning" is the most important while "increase turnaround time" is the least important.
Vita.
Thesis (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Technical services (Libraries) -- Contracting out -- Philippines -- Manila Metropolitan Area; Academic libraries -- Philippines -- Manila Metropolitan Area; Special libraries -- Philippines -- Manila Metropolitan Area